"Crime against Humanity" or "Crime against Jews"? Acknowledgment in Construals of the Holocaust and Its Importance for Intergroup Relations. (7th March 2013) - Vollhardt, Johanna Ray
<x xml:space="preserve">Abstract</x> This article examines the consequences of different representations of the Holocaust for intergroup relations, focusing on the role of acknowledgment of different groups' fate that is inherent in these construals. Holocaust representations have become increasingly universal. Research on recategorization suggests prosocial outcomes of such superordinate representations. However, among minority groups, acknowledging both superordinate and subgroup identities may be crucial in order to prevent backlash. An experimental study among Jewish and non‐Jewish participants (N = 163) was conducted to test these ideas. As hypothesized, prosocial responses to outgroup victims of collective violence and acknowledgment of their suffering increased among Jewish participants when both a superordinate categorization of the Holocaust and subgroup (Jewish) fate were presented, compared to when only one of these categorizations were used. Conversely, different categorizations did not affect outcomes among the control group. Practical implications for intergroup relations and memorialization in the aftermath of genocide are discussed.